The impact of perception and presence on emotional reactions: a review of research in virtual reality - Diemer, Julia; Alpers, Georg W.; Peperkorn, Henrik M.; Shiban, Youssef; Mühlberger, Andreas (Frontiers in Psychology, 2015)
Abstract is inlcuded in the main text file due to technial problems.